Green Fund Ownership and Return on Assets on the Total Assets of Coal Mining Companies Listed on the Indonesia Stock Exchange - Firman Firman; Heriswanto Heriswanto; Mahfudnurnajamuddin Mahfudnurnajamuddin (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: The study aims to determine the effect of green fund ownership and return on assets on total assets in coal companies listed on the Indonesia Stock Exchange. Green fund ownership is proxied by ESG ownership, while profitability is proxied by return on assets (ROA). Research Method: This research used a quantitative approach using secondary data. The sample selection technique used purposive sampling, with 10 companies sampled at four-year intervals, resulting in a total sample of 40 companies. The data analysis methods used were descriptive analysis, classical assumption tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression tests, T-tests, and F-tests using the Statistical Package for the Social Sciences (SPSS) application. Results and Discussion: The findings of this study indicate that green fund ownership and return on assets each have a positive and significant effect on total assets in coal companies listed on the Indonesia Stock Exchange (IDX). Implications: The results reinforce the argument that institutional investors with environmental, social, and governance (ESG) preferences may encourage firms to adopt sustainable business practices, thereby enhancing their ability to attract capital and expand their asset base. Originality: This research contributes empirical evidence from an emerging economy, specifically Indonesia, where studies investigating the interaction between ESG-oriented ownership, financial performance, and corporate asset growth remain limited.